Cardiovascular safety of central nervous system stimulants in children and adolescents: population based cohort study. (18th July 2012) - Winterstein, Almut G; Gerhard, Tobias; Kubilis, Paul; Saidi, Arwa; Linden, Stephan; Crystal, Stephen; Zito, Julie; Shuster, Jonathan J; Olfson, Mark
Abstract : Objectives To evaluate the cardiac safety of central nervous system stimulants in children and adolescents. Design Population based retrospective cohort study. Setting Automated healthcare claims data from 1 219 847 children and young people eligible for 28 state Medicaid programmes from 1999 to 2006 linked to the Social Security Death Master File and the National Death Index. Participants Children and young people age 3-18 entered the cohort at the first diagnosis of a mental health condition commonly treated with stimulants (such as attention-deficit/hyperactivity disorder) after a minimum period of six months' eligibility and were followed until loss of eligibility, their 19th birthday, admission to hospital for longer than 30 days, or death. Exclusion criteria included transplant recipients, receipt of dialysis, or claims indicating substance misuse. We retained high risk groups with similar use of stimulants as low risk children (such as children with congenital heart disease). Sociodemographic characteristics, cardiac risk factors, and psychiatric diagnoses obtained from before the index period were summarised with a propensity score. We used discrete survival analysis to estimate the relative risk for periods of stimulant use and non-use, adjusted for propensity score and antipsychotic use for the full cohort and the high risk and low risk groups. Main outcome measures Composite endpoint of stroke, acute myocardial infarction, or sudden cardiac death; a secondary composite endpoint added ventricular arrhythmia Results A total of 66 (95 including ventricular arrhythmia) events occurred during 2 321 311 years of follow-up. The odds ratio adjusted for propensity score and antipsychotic use for current versus no stimulant use was 0.62 (95% confidence interval 0.27 to 1.44), with a corresponding adjusted incidence rate of 2.2 and 3.5 per 100 000 patient years for current stimulant and non-use, respectively. Twenty six events occurred in high risk patients (incidence rate 63 per 100 000 patient years) with an odds ratio of 1.02 (0.28 to 3.69). Odds ratios for the secondary endpoint were similar to those for the primary endpoint (0.74, 0.38 to 1.46). Conclusions Treatment of children with central nervous stimulants is not significantly associated with an increase in the short term risk of severe cardiac events. Analyses cannot be generalised to children with long term use of stimulants. Furthermore, long term effects of slight increases in heart rate or blood pressure are unknown.